AB0163 Comprehensive Analysis of Circulating Mirnas in Patients with Axial Spondyloarthritis. (10th June 2014) - Prajzlerová, K.; Fojtíková, M.; Forejtová, Š.; Jüngel, A.; Gay, S.; Pavelka, K.; Vencovský, J.; Šenolt, L.; Filková, M.
Abstract : Background: Differential expression of miRNAs and altered regulation of their target genes has been shown to contribute to pathophysiology of many diseases. In addition, circulating miRNAs may serve as diagnostic and/or prognostic biomarkers. Objectives: To analyse a large set of cell-free circulating miRNAs in patients with axial spondyloarthritis (AxSpA) and to investigate their relationship with spinal involvement. Methods: Total RNA was isolated using phenol-chloroform extraction from plasma of 5 healthy controls (HC), 5 patients with non-radiographic AxSpA (nr-AxSpA) and 10 patients with radiographic AxSpA (5 patients with radiographic sacroiliitis and no spinal involvement; 5 patients with the presence of syndesmophytes). Equal amount of RNA was used for reverse transcription. MiRNAs were analysed using TaqMan® Low Density Array (Applied Biosystems). dCt method was used for relative quantification as follows: dCt = Ct(miRNA) − Ct(array average). Average of dCt for single miRNA was used for further x-fold calculation. Results: Out of total 760 miRNAs, 162 miRNAs were detected in a group of HC, 156 miRNAs in patients with nr-AxSpA and 110 in patients with radiographic AxSpA. All patients with AxSpA had at least 2-fold lower levels of 56 miRNAs, e.g. miR-27a, miR-146a and miR-181a (8 of them at least 5-fold), while showed at least 2-fold higher levels of 4 miRNAs when compared with HC. In patients with radiographic AxSpA, 75 miRNAs were of at least 2-fold lower levels (14 of them at least 5-fold), while 3 miRNAs were of at least 2-fold higher levels in comparison with the group of nr-AxSpA patients and HC. Following changes were observed in patients with AxSpA with a progressing degree of spinal involvement: In patients with nr-AxSpA, 18 miRNAs showed at least 2-fold decrease (3 of them at least 5-fold), while 9 miRNAs showed at least 2-fold increase in comparison with HC. In patients with radiographic AxSpA with no spinal involvement, 71 miRNAs showed at least 2-fold decrease (13 of them at least 5-fold), while 6 miRNAs showed at least 2-fold increase in comparison with nr-AxSpA. In patients with radiographic AxSpA with a presence of syndesmophytes, 6 miRNAs showed at least 2-fold decrease, while 15 miRNAs showed at least 2-fold increase in comparison with radiographic AxSpA presenting with no spinal involvement. Importantly, 4 miRNAs showed at least 1.5-fold decrease in levels across all stages with progressing spinal damage. Conclusions: Comprehensive analysis of cell-free circulating miRNAs revealed differential expression of several miRNAs in patients with AxSpA according to different stages of the disease. Some of these deregulated miRNAs were shown to play a role in innate immunity and new bone formation. This data suggest involvement of miRNAs in the process of AxSpA development and their potential use as biomarkers of disease severity. Acknowledgements: This work was supported by IGA project no. NT 14498, project of MHCR for conceptual development of research organization 023728 and BT-Cure Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4091